Motvilliga vittnen - Lovisa Andén (Föreningen för utgivande av Tidskrift för litteraturvetenskap, 2022)
Reluctant Witnesses: Swedish Memoirs from the Soviet Karelian Purges Several hundred Swedes emigrated to Soviet Karelia in the beginning of the 1930s. Many of them remained there when the Great Terror began, and they became targets of repression. As of now, there is no coherent public narrative in Sweden that acknowledge the Swedish survivors; most survivors never talked publicly about their experiences, let alone wrote about them, and the few who did, did so reluctantly. This article discusses four memoirs written by Swedish survivors of the Soviet repression and the silence that still surrounds these memoirs. The narratives themselves, as well as the reception of the narratives, bear witness to the difficulty of narrating experiences that have not yet been publicly acknowledged. Based on the Swedish witness accounts, this article aims to examine 1) the difficulty of testifying in the absence of a public narrative, and 2) the ability of witness literature to challenge and change established historical narratives.